Greenhouse gas emissions from road transport in South Africa and Lesotho between 2000 and 2009. (June 2015) - Tongwane, Mphethe; Piketh, Stuart; Stevens, Luanne; Ramotubei, Teke
Highlights: Road transportation produced 43.5 MtCO2 -eq in South Africa in 2009. Motorcars and trucks make a combined 70% of total emissions from road transport. Gauteng, the economic capital of Africa is the largest producer of road emissions. Road transport emissions are unsustainable increasing with time. Over-worked minibus taxis have lowest modal intensities compared. Abstract: Road transport is the major source of global greenhouse gas emissions from the transport sector, contributing about three quarters towards the total transport emissions. This study used the Intergovernmental Panel on Climate Change Tier 2 approach to calculate greenhouse gas emissions from road transport in South Africa and Lesotho between 2000 and 2009. Key transport emitting sources, trend analysis and modal intensities were determined for the two countries. For South Africa, provincial road transport emissions were calculated from the number of vehicles by vehicle type and distance travelled. Calculations were at a national level in Lesotho. Road transport carbon dioxide equivalent emissions were estimated at 43.5 million tonnes in South Africa and 0.28 million tonnes in Lesotho in 2009. Motorcars and trucks produced 70.6% of the total road transport emissions in South Africa. Road transport emissions increased by approximately 2.6% per year between 2000 and 2009 in South Africa, while they increased by approximately 2.5% per annum in Lesotho over the same period. Gauteng province had the highest emissions, contributing approximately a third of total road transport emissions in South Africa; while the Northern Cape contributed only 2%. Minibus taxis were the most efficient transport mode on the basis of load carried. The Northern Cape had the highest emissions per passenger-kilometres and tonne-kilometre while the North West had the lowest. Trend assessment showed that emissions from trucks increased rapidly while emissions from other modes of transport decreased over the study period.